(untitled) (Research, Society and Development, 2022)
Introduction: Cancer is one of the most complex public health problems in Brazil, with a high degree of morbidity and mortality. However, it has effective therapeutic methods, such as chemotherapy, where nurses are active in this process. Objective: To report the experience lived by a resident nurse, who worked in the oncology sector, administration of intravenous chemotherapy. Methodology: Descriptive study, type of experience report, elaborated from the experience of this nurse in the oncology sector of her in-service training unit. Development: The resident nurse had the opportunity to develop theoretical and practical knowledge, in order to promote a complete and quality care to cancer patients. Conclusion: The study was of great value to highlight the importance of the nursing residency program and may lead to the development of new research on the subject.